1989
DOI: 10.1351/pac198961112047
|View full text |Cite
|
Sign up to set email alerts
|

Use of thermally modified carbon black and carbon molecular sieve adsorbents in sampling air contaminants

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Furthermore, TCR has been used as an adsorbent for the removal of naphthalene, toluene, xylene, cadmium(II), mercury(II), lead(II) and Cu(II) (Rowley et al 1984;Gunasekara et al 2000;Entezari et al 2006;Calisir et al 2009;Alamo-Nole et al 2011). CB has been used as an adsorbent for the removal of chlorophenols, p-nitrophenol, toluene and xylene from aqueous solutions (González-Martín et al 1994;Domínguez-Vargas et al 2009;Alamo-Nole et al 2011) and as a molecular sieve for sampling air contaminants (Betz and Supina 1989). Therefore, the presence of CB in TCR is expected to contribute in the removal of contaminants by adsorption (Alamo-Nole et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TCR has been used as an adsorbent for the removal of naphthalene, toluene, xylene, cadmium(II), mercury(II), lead(II) and Cu(II) (Rowley et al 1984;Gunasekara et al 2000;Entezari et al 2006;Calisir et al 2009;Alamo-Nole et al 2011). CB has been used as an adsorbent for the removal of chlorophenols, p-nitrophenol, toluene and xylene from aqueous solutions (González-Martín et al 1994;Domínguez-Vargas et al 2009;Alamo-Nole et al 2011) and as a molecular sieve for sampling air contaminants (Betz and Supina 1989). Therefore, the presence of CB in TCR is expected to contribute in the removal of contaminants by adsorption (Alamo-Nole et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the chalcophilic metals, it was suggested that cross-linked sulfur serves as sorption sites (Rowley at al., 1984). Carbon black has also been frequently used as adsorbent of solutes from aqueous solution (González-Martín et al, 1994;Takeda et al, 1998;Domínguez-Vargas et al, 2009) and as molecular sieve (Betz and Supina, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of sorbent tubes and TD over whole air samplers are the tubes' small size and portability, lower cost, increased ability to transfer less volatile (C10 and greater) and polar compounds, and reusability without a cleaning step (Bianchi and Varney, 1993;Ciccioli et al, 1992;Woolfenden, 1997). Drawbacks of the tubes are the limited ability to sample the most volatile compounds (<C4), the presence of artefacts, the need to refrigerate unanalysed samples, and the requirement for a sampling pump (Betz and Supina, 1989;Bianchi and Varney, 1993;Ciccioli et al, 1992;Woolfenden, 1997). Due to their reusability, stability, and small size, sorbent tube sampling (sometimes referred to as "gas sampling cartridges") provides an attractive method for low-cost, portable sample collection.…”
mentioning
confidence: 99%